2012
DOI: 10.1007/s10040-012-0832-8
|View full text |Cite
|
Sign up to set email alerts
|

The interference of a deep thermal system with a shallow aquifer: the case of Sodere and Gergedi thermal springs, Main Ethiopian Rift, Ethiopia

Abstract: An integrated survey program involving geological, hydrogeological and geophysical techniques has been employed to characterize the aquifer geometry, recharge and circulation dynamics of thermal springs within a shallow aquifer system in Ethiopia. The selected springs for the case study are Sodere and Gergedi, which are situated within the tectonically active Main Ethiopian Rift (MER). Geologically, the studied springs are located on PlioQuaternary volcanic rocks. The geophysical results indicate the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Since the high conductivities in MT show zones of partial melt currently in the crust, while the gravity data are sensitive to time-averaged locus of intrusion, we suggest that the locus of magma migration from depth beneath the TMGP has changed through time. Haile and Tamiru. (2012) showed that the Gedemsa caldera hosts a geothermal system and is the heat source for the Geregendi thermal spring.…”
Section: Geothermal Heat Sources and Roles Of Subsurface Structures I...mentioning
confidence: 99%
“…Since the high conductivities in MT show zones of partial melt currently in the crust, while the gravity data are sensitive to time-averaged locus of intrusion, we suggest that the locus of magma migration from depth beneath the TMGP has changed through time. Haile and Tamiru. (2012) showed that the Gedemsa caldera hosts a geothermal system and is the heat source for the Geregendi thermal spring.…”
Section: Geothermal Heat Sources and Roles Of Subsurface Structures I...mentioning
confidence: 99%
“…Natural variation of isotopic signatures can be used to determine water source and subsequent alteration processes. The origin of Ethiopian geothermal waters is predominantly from local meteoric water (Beyene, 2000; Haile & Abiye, 2012; Teclu, 2003, 2006). A generally linear relationship exists between δ 2 H and δ 18 O called the global meteoric water line (GMWL; Craig, 1961).…”
Section: Synthetic Review Of Ground and Surface Water Hydrochemical Datamentioning
confidence: 99%
“…Characteristics of springs (especially hot springs) in orogenic regions are due to the interaction between water, the lithosphere, and environmental conditions like lithology, pathways, residence time underground, and many other factors. The origin of elevated temperatures in hydrothermal reservoirs (hot/warm springs) can be due to the geothermal gradient with deep circulation of groundwater through faults, chemical reactions (e.g., in evaporates and oil field brines), heat produced through radioactive decay of longlived radioactive material (isotopes), and mixing of meteoric water with magmatic water or volcanic vapour in volcanic area [1][2][3][4][5][6][7][8][9][10][11]. The hydrothermal phenomenon most often occurs where the released water and vapour are related to regional volcanic activities.…”
Section: Introductionmentioning
confidence: 99%